PENGEMBANGAN KOMIK MATEMATIKA BTVH UNTUK SISWA KELAS VIII SMP - Mualifatul Munawaroh; Heny Sulistyaningrum (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2019)
Mathematics is a subject that is quite difficult because it contains calculations, symbols, and abstract concepts. Learning mathematics in SMP Negeri 1 Jenu has never used a mathematics comic. This research is to produce a product in the form of a mathematical comic BTVH (based on Van Hiele's theory). This study aims to: 1) describe the development of BTVH mathematics comics for VIII grade students of SMP Negeri 1 Jenu, 2) describe the quality of the development of BTVH mathematics comics for VIII grade students of SMP Negeri 1 Jenu. This research is a development research with ADDIE model. This model consists of five stages, namely the analysis phase (Analysis), the product design stage (Design), the product development stage (Development), the implementation phase (Implementation), the evaluation stage (Evaluation). BTVH mathematical comics contains 5 story stages, namely stage 1 (introduction), stage 2 (analysis), stage 3 (sequencing), stage 4 (deduction), and stage 5 (accuracy). Data collection instruments are divided into three, namely validity, practicality, and effectiveness. The data analysis technique used is descriptive statistical data analysis techniques. The results of this study are the BTVH math comics to improve student mathematics learning outcomes. After going through the stages of validation and testing of mathematical comics it was declared very good. The percentage of validity data is 96%, the percentage of practicality data is 90%, and the percentage of effectiveness data is 93%.